Examining the Loopholes in the criminal justice system of Iran and Indonesia in relation to piracy crimes - Rahmanian, Abdul Majid; Talebpour, Mansour; Raijian Asli, Mehrdad (Jurnal Cita Hukum, 2022)
Due to the chaos produced by piracy in Indonesia, Southeast Asian sea areas have become hazardous for ships. On the other hand, Iran's shortage of modern maritime laws has rendered it impossible to defend Iran's rights in the region's waters. This study seeks to investigate the piracy-related gaps in the Iranian and Indonesian criminal justice systems. Using an analytical-comparative methodology, this study examined the issue theoretically. The required data and information were gathered using the library method, books, and articles. According to the results of the investigations, the most significant common flaws in the maritime law of Iran and Indonesia are the lack of specialized maritime judges and experts, the disparity in the punishment of pirates, the lack of educational facilities regarding naval law, the lack of careful and appropriate attention to the maritime conventions, and the disparity in the punishment of pirates. Based on the results of the research, it is suggested that the navies of Iran and Indonesia hold joint courses for officers, particularly young officers, to cooperate in combating maritime terrorism and piracy and exchange information in order to combat naval terrorism and piracy, as well as train and trade marine science lawyers and judges.